Acacia catechu (Katha) and its Medicinal Applications: A Review - Danish, Ansari Mohd; Alam, Saiyad Shah (Pharmacognosy Reviews)
This review aims to have deep intensive knowledge about the general description and medicinal uses of Acacia catechu. Catechu is an extract of the wood of the Khair tree. This has been used for centuries throughout the world to treat several diseases. The drug has been in use for the treatment of infection, inflammation, pain management, skin diseases, and wounds. Recent studies have exhibited that this drug contains several phytochemicals that possess antimutagenic activities in cancer cells. The drug has also been used for the treatment of skin non-healing ulcers. This review article has demonstrated the different chemical constituents imparting in the healing of wounds/ulcers.
Keywords: Acacia catechu; Tannins; Fisetin; Catechin; Cyanidanol; Unani medicine; Non healing ulcers